Outbreak of Tuberculosis in a Colony of Rhesus Monkeys (Macaca mulatta) after Possible Indirect Contact with a Human TB Patient. Issue 2 (August 2015) - Mätz-Rensing, K.; Hartmann, T.; Wendel, G.M.; Frick, J.S.; Homolka, S.; Richter, E.; Munk, M.H.; Kaup, F.-J.
Summary: Simian tuberculosis is one of the most important bacterial diseases of non-human primates. Outbreaks of tuberculosis have been reported in primate colonies almost as long as these animals have been used experimentally or kept in zoological gardens. Significant progress has been made in reducing the incidence of tuberculosis in captive non-human primates, but despite reasonable precautions, outbreaks continue to occur. The most relevant reason is the high incidence of tuberculosis (TB) amongst the human population, in which tuberculosis is regarded as an important re-emerging disease. Furthermore, many non-human primate species originate from countries with a high burden of human TB. Therefore, Mycobacterium tuberculosis remains a significant threat in animals imported from countries with high rates of human infection. We report an outbreak of tuberculosis among a group of rhesus monkeys ( Macaca mulatta ) living in a closed, long-term colony. The outbreak coincided with reactivation of a TB infection in a co-worker who never had direct access to the animal house or laboratories. Eleven of 26 rhesus monkeys developed classical chronic active tuberculosis with typical caseous granulomata of varying size within different organs. The main organ system involved was the lung, suggesting an aerosol route of infection. Such an outbreak has significant economic consequences due to animal loss, disruption of research and costs related to disease control. Precautionary measures must be improved in order to avoid TB in non-human primate colonies.